1990
DOI: 10.1002/bjs.1800770927
|View full text |Cite
|
Sign up to set email alerts
|

Elective resection for diverticular disease of the sigmoid colon

Abstract: From 1966 to 1987, 177 consecutive patients were operated on electively for diverticular disease of the sigmoid colon. The indications for surgery were: colovesical fistula (n = 12), suspicion of residual abscess (n = 39), two or more previous attacks of acute inflammation (n = 52), chronic symptoms (n = 72) and suspicion of carcinoma (n = 2). An abscess was found at operation in 76 patients (43 per cent) and this was extracolic with local peritonitis in 52 patients (29 per cent). An unsuspected abscess was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
2
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 11 publications
5
39
2
1
Order By: Relevance
“…Thus, given the lack of efficacy of antibiotics and surgical resolution of pain, we recommend surgical intervention promptly in those patients presenting with atypical or chronic/smoldering symptoms in which all other diagnoses have been excluded. Similar to our results, Moreaux et al [21] reported the outcome of 72 patients who underwent sigmoid resection for chronic symptoms. As in our series, unsuspected abscess was discovered in 24 patients and symptoms of pain resolved in 59 patients.…”
Section: Introductionsupporting
confidence: 82%
“…Thus, given the lack of efficacy of antibiotics and surgical resolution of pain, we recommend surgical intervention promptly in those patients presenting with atypical or chronic/smoldering symptoms in which all other diagnoses have been excluded. Similar to our results, Moreaux et al [21] reported the outcome of 72 patients who underwent sigmoid resection for chronic symptoms. As in our series, unsuspected abscess was discovered in 24 patients and symptoms of pain resolved in 59 patients.…”
Section: Introductionsupporting
confidence: 82%
“…Although there was endoscopic evidence of diverticulitis in only 13 per cent, on pathological examination it was found that 76 per cent had histological evidence of acute and chronic mucosal inflammation. In addition, seven patients had a previously undiagnosed pericolic abscess which is a feature not uncommonly encountered in patients having colonic resection for symptomatic diverticular disease 58,59 (although they are often small and hidden in the surrounding fatty tissue) 14 . Over three-quarters of the 47 patients had complete resolution of symptoms after surgery.…”
Section: Inflammatory Changesmentioning
confidence: 99%
“…Until recently a two-staged procedure, usually as described by Hartmann [11, 12], has been the most common method for treating patients who require emergency surgery for complicated diverticular disease of the sigmoid colon [5,6,7,8,9,10,13,14,15,16], but it is also used when technical difficulties are encountered in electively operated patients [17, 18]. …”
Section: Introductionmentioning
confidence: 99%